A Hardware-in-the-Loop Platform for DC Protection - (:unkn) unknown (My University, 2020)
With the proliferation of power electronics, dc-based power distribution systems can be realized; however, dc electrical protection remains a significant barrier to mass implementation dc power distribution. Controller Hardware-in-the-loop (CHiL) simulation enables moving up technology readiness levels (TRL) quickly. This work presents an end-to-end solution for dc protection CHiL for early design exploration and verification for dc protection, allowing for the rapid development of dc protection schemes for both Line-to-Line (LL) and Line-to-Ground (LG) faults. The approach combines using Latency Based Linear Multistep Compound (LB-LMC), a real-time simulation method for power electronic, and National Instruments (NI) FPGA hardware to enable dc protection design with CHiL. A case study is performed for a 1.5 MW Voltage Source Rectifier (VSR) under LL and LG faults in an ungrounded system. The deficiency in real-time simulation resolution of Commercial-off-the-Shelf (COTS) for dc fault transients is shown, and addressed by using LB-LMC RT solver inside NI FPGA hardware to achieve 50 ns resolution of dc fault transients.
Keywords: Controller Hardware-in-the-Loop; dc protection; fault protection; Hardware-in-the-Loop; Power Electronics; real-time simulation